Primer of Epidemiology - Friedman, Gary D. (McGraw-Hill, Medical Pub. Division, 2004)
A concise introduction to epidemiology. Covers all the basics: methods of study, how to conduct a study, and multivariate analysis. Features updated case studies, which make the critical link between epidemiology, clinical research, and patient care.